Study on the trade-off/synergy spatiotemporal benefits of ecosystem services and its influencing factors in hilly areas of southern China - Tan, Fenglian; Lu, Zhaoyan; Zeng, Fusheng (Frontiers in Ecology and Evolution, 2024)
This study aims to investigate the factors influencing ecosystem service trade-offs/synergies(TOSs) in major agricultural production areas in the southern hilly region and to propose optimization strategies to promote ecosystem sustainability in agricultural areas. The study used geographical detector to analyze the determinants influencing the ecosystem service trade-offs as well as correlation analysis, Geographically Weighted Regression (GWR), and geographical detector to analyze the spatial and temporal evolution of ecosystem service and TOSs relationships from 2000 to 2020 in Hunan Province. The results showed that the comprehensive value of ecosystem services in Hunan Province showed an increasing trend from 2000 to 2020. With spatial heterogeneity, the areas with high values were mainly distributed in the hilly areas in the west, south and east of Hunan Province, and the areas with low values were mainly distributed in the Dongting Lake Plain and the Xiangzhong Hilly Basin. There was a trade-offs relationship between food production (FP) and all other ecosystem services, of which FP has the strongest trade-offs effect with habitat quality (HQ). The synergies effect between HQ, water yield (WY), carbon storage (CS) and soil conservation (SC) shows an increasing trend. Gross Domestic Product (GDP) and SLOPE are the dominant factors for the strength of trade-offs between food supply and other ecosystem services, and Digital Elevation Model (DEM) and Normalized Difference Vegetation Index (NDVI) are the dominant factors for the strength of synergies effects among ecosystem services. The strength of TOSs effects of ecosystem services is determined by interactions or co-influences between the two services rather than by a single component. The results of this study can provide a reference basis for the enhancement of ecosystem services and the sustainable planning of agricultural landscapes in the southern hilly areas.